The Criteria for Selecting German Coursebooks in Indonesian Upper Secondary Schools: Critical Appraisal from Teachers View - Aditya Rikfanto; Retna Indah Sri Mulyati (International Journal of Language Teaching and Education, 2021)
Curriculum changes directly impact learning objectives, content selection, and the use of coursebooks as learning resources. In reality, teachers tend to choose coursebooks that are different from the curriculum direction. This study aims to determine how teachers view the selection of German coursebooks and what criteria they used to decide coursebooks for teaching in secondary school. Respondents were 20 teachers in Yogyakarta and Central Java. We use a qualitative descriptive approach to analyse interview-based data and records through reduction techniques, categorisation, verification and conclusion. The results showed that 75% of teachers want to choose books independently, not determined by the national curriculum on a mandatory level. This study proposed thirteen criteria for book selection based on the data analysis obtained from respondents. From these criteria, teachers can make priority choices and apply selected coursebooks to lessons.